Basaloid squamous cell carcinoma arising in an inverted papilloma in the nasal cavity: A case report and review. Issue 5 (October 2017) - Koyama, Satoshi; Nakamura, Yosuke; Yokoyama, Yuko; Morisaki, Tsuyoshi; Fukuhara, Takahiro; Fujiwara, Kazunori; Kitano, Hiroya; Takeuchi, Hiromi
Abstract: Basaloid squamous cell carcinoma (BSCC) is a histologically distinctive variant of squamous cell carcinoma comprising basal cell carcinoma and squamous cell carcinoma. BSCC is aggressive and shows a poor prognosis because of frequent lymph node invasion and distant metastases. BSCC preferentially occurs in the cervix, thymus, and esophagus and is uncommonly found in the head and neck region. BSCC in the nasal cavity or paranasal sinus is particularly rare. Inverted papilloma is an uncommon, benign tumor with a propensity to be associated with malignancy; however, BSCC arising in an inverted papilloma has never been reported. Here we report a case of a 56-year-old woman with BSCC arising in an inverted papilloma in the nasal cavity. The woman was referred to our hospital for epistaxis, nasal congestion, and dysphagia. A tumor was observed to completely occupy the left nasal cavity. The biopsy specimen was histologically diagnosed as papilloma. Computed tomography demonstrated a tumor with heterogeneous contrast effect occupying the left nasal cavity; however, extra-nasal tract extension was not observed. We performed endoscopic excision of the tumor. Microscopic findings confirmed the diagnosis of BSCC arising from an inverted papilloma. No tumor recurrence has been observed for 13 months after surgery.